Analisis Perancangan Event Kemah Budaya "Milangkara Warisan Cikalahang" sebagai Media Edukasi Budaya dan Promosi Desa Wisata Cikalahang Kabupaten Cirebon - Fitriatunnisa Shabrina; Ety Setiawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to examine the design of the “Milangkara Warisan Cikalahang” Cultural Camp Event as a medium for cultural education and a promotional strategy for Cikalahang Tourism Village in Cirebon Regency. This research employed a qualitative approach with a document analysis design to explore the event planning process comprehensively. Data were collected from event planning documents, including the event concept, objectives, participant targets, rundown, promotional strategies, publication media, site layout, budget plan, and stakeholder collaboration forms. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that the event was designed based on experiential learning, enabling participants to understand local cultural values through direct experiences such as cultural trekking, botram communal dining, pencak silat training, Jaipong dance lessons, and traditional games. The promotional strategy combined digital and conventional media to strengthen the image of Cikalahang Tourism Village as a cultural tourism destination. Furthermore, collaboration among stakeholders supported systematic event preparation. The study concludes that well-structured event planning is essential for successful cultural event implementation and sustainable tourism promotion.